1984
DOI: 10.1126/science.6324345
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Reactive with Human T-Lymphotropic Retroviruses (HTLV-III) in the Serum of Patients with AIDS

Abstract: In cats, infection with T-lymphotropic retroviruses can cause T-cell proliferation and leukemia or T-cell depletion and immunosuppression. In humans, some highly T4 tropic retroviruses called HTLV-I can cause T-cell proliferation and leukemia. The subgroup HTLV-II also induces T-cell proliferation in vitro, but its role in disease is unclear. Viruses of a third subgroup of human T-lymphotropic retroviruses, collectively designated HTLV-III, have been isolated from cultured cells of 48 patients with acquired im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
281
0
6

Year Published

1984
1984
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,067 publications
(293 citation statements)
references
References 23 publications
6
281
0
6
Order By: Relevance
“…The HTLV-I subgroup is etiologically linked with adult T-cell leukemia-lymphoma (ATLL) (1), whereas HTLV-III is associated with the acquired immunodeficiency syndrome (AIDS) (2)(3)(4)(5). A distantly related human T-cell virus, designated HTLV-II, has been isolated from one patient with a T-cell variant of hairy cell leukemia (6)(7)(8) and from one intravenous drug user with AIDS (9).…”
mentioning
confidence: 99%
“…The HTLV-I subgroup is etiologically linked with adult T-cell leukemia-lymphoma (ATLL) (1), whereas HTLV-III is associated with the acquired immunodeficiency syndrome (AIDS) (2)(3)(4)(5). A distantly related human T-cell virus, designated HTLV-II, has been isolated from one patient with a T-cell variant of hairy cell leukemia (6)(7)(8) and from one intravenous drug user with AIDS (9).…”
mentioning
confidence: 99%
“…The relationship between p24 antibody reactivity and clinical status has been described previously [2,[8][9][10][24][25][26]. Cross-sectional studies have reported higher p24 antibody titers in early infection, and prospective studies decreasing titers (and occasional loss of the p24 band) in patients progressing to AIDS [8].…”
Section: Discussionmentioning
confidence: 92%
“…The Western blot includes nine principal bands which represent the presence of antibodies to various viral components [1,2] and is the main confirmatory test for the diagnosis of HIV infection [3][4][5][6]. It has been reported that almost all individuals exposed to HIV from transfused blood will develop antibodies within three months [7], but it is unclear whether the nature of the antibody response influences the rate of loss of CD4+ lymphocytes or progression to AIDS, and the prognostic implications of specific antibodies to HIV remain uncertain [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…We have isolated H1LV-III from a majority of pre-AIDS patients and a large number of actual AIDS patients [11], but isolation from the normal population is rare. Almost all AIDS and pre-AIDS patients have antibodies to H1LV-III [42]. A typical Western blot is shown in Fig.…”
Section: F Htlv-i1i and Aidsmentioning
confidence: 99%